O efeito da idade sobre a latência do potencial evocado auditivo P300 - Cóser, Maria José Santos (2007)
This study aimed to estimate age related effects over the latency of P300 auditory potential within an elderly group. P300 latencies were measured in 62 healthy elderly subjects with pure tone thresholds of 1000 and 2000Hz equal or smaller than 40 dBNA, from both genders, 19 with ages between 60 e 64 years old (Group 60), 22 with ages between 65 and 69 years old (Group 65) and 21 with ages between 70 e 74 years old (Group 70). P300 latencies in response to rare 2000 Hz, 80 dBHL tone bursts randomly presented in 1/5 relationship with a frequent 80 dBHL, 1000 Hz tone burst were measured in all of them. Statistic analysis was made using with Variance Analysis (ANOVA) test, with its minimal significant differences Duncan test. In order to estimate the effect of age upon the latency of P300 was used the Linear Regression Coefficient. Data were submitted to the SAS 8.02 test and 5% significance level was adopted. Group 60 presented P300 latency of 337, 26 ms (SD 11, 31), Group 65 presented P300 latency of 351, 86 ms (SD 29,05) and Group 70 presented latency of 370, 19 ms (SD 23, 40). The linear regression of the all 62 elderly subjects P300 latencies showed a 2, 85 ms/year growth in the 60 - 74 years range. Statistics analysis showed that these were significant findings so P300 latency differs in the three studied groups and present tendency to growth with the age growing. In conclusion, the present study showed that P300 latency grows with aging in a significant way; this growing was of 2, 85 ms/year in the 60 74 years range.